THE EFFECT OF GOVERNMENT SPENDING IN THE EDUCATION SECTOR AND EMPLOYMENT OPPORTUNITIES ON THE HUMAN DEVELOPMENT INDEX IN INDONESIA, 2015-2019 - Amalia, Hasima Sefiana (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine the Influence of Government Expenditure of Education Sector and Employment Opportunities for Human Development Index in Indonesia during 2015-2019. The type of data in this study is secondary data which is quantitative data from 34 provinces (Nangroe Aceh Darussalam, North Sumatra, West Sumatra Province, Riau, Riau Islands, Jambi, South Sumatra, Bangka Belitung, Bengkulu, Lampung, DKI Jakarta, West Java, Banten, Central Java, DI Yogyakarta, East Java, Bali, West Nusa Tenggara, East Nusa Tenggara, West Kalimantan, Central Kalimantan, South Kalimantan, East Kalimantan, North Kalimantan, North Sulawesi, West Sulawesi Province, Central Sulawesi, Southeast Sulawesi, South Sulawesi, Gorontalo, Maluku, North Maluku, West Papua, Papua) of Indonesia during 2015-2019. The analysis used is panel data regression analysis with a fixed effect regression model as the selected model and uses the Eviews 9 application obtained from the Central Statistics Agency (BPS) and DJPK KEMENKEU. The data analysis technique used in this study was panel data regression analysis. By using a panel data regression analysis model, the output shows that Government Expenditure of Education Sector (X1) has a positive and significant effect of Human Development Index (Y) in Indonesia. Employment opportunity (X2) has a positive and significant effect of Human Development Index (Y) in Indonesia.